(untitled) (Research, Society and Development, 2022)
Objective: to demonstrate the perception of preceptors regarding the teaching-service integration in the execution of the preceptorship activity. Methodology: This is a qualitative, descriptive study, of the intervention type, in which the strategy of Permanent Education in Health was applied for the acquisition of knowledge about preceptorship. Eight preceptors were interviewed and the semi-structured interview was analyzed using the Bardin method. Results and Discussion: The preceptors reported that the integration between teaching and service occurs in a disjointed way. For the success of the preceptorship activity, planning should occur with the involvement of all, in a cohesive and agreed way. However, they realize that the preceptors themselves need to be more active and knowledgeable about their educational role in carrying out this activity. Conclusion: the existing fragility in the integration between the service and teaching, and the observation by preceptors of the need for them to be more active in this process, demonstrates the need to create new strategies that alleviate this situation. The educational meetings favored the discussion of the theme and the encouragement to search for an adequate integration between the service and teaching. This vision facilitates the search for the achievement of what is recommended by the National Curriculum Guidelines regarding training, and the correct use of the environment of the Unified Health System.